Model Pengembangan Zakat Produktif di Masjid Jami’ Al-Baitul Amien Jember sebagai Pemberdayaan Ekonomi Umat - Achmad Faqih Supandi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
This research focuses on models, concepts, practices and the role of the Mosque-Based Economy in the perspective of Islamic economics in the Masjid Jamik Al Baitul Amien in improving Community Welfare. The purpose of this study is to describe the models, concepts, practices and roles of mosque-based economics in the perspective of Islamic economics in the Masjid Al-Baitul Amin Jember. This research method uses a qualitative approach with a descriptive type, this is because researchers want to describe the Model of Mosque-Based Economic Development in the Islamic Economic Perspective at the Jamik Al-Baitul Amien Mosque in Jember Regency 2015. The results of the study show that the economic economic model of the Ummah uses financing or the provision of facilities by providing funds in accordance with sharia principles. To support investments that have been planned based on an agreement between the institution and other parties, financed by the concept of optimizing productive Zakat or better known as micro business loans without interest that can burden small communities, so that people can meet their economic needs. Then the capabilities possessed by the Jami Mosque 'Al-Baitul Amin Jember are professional human resources, strategic location, adequate infrastructure and sufficient facilities for the economic empowerment of the Ummah.